Efektivitas Pengawasan Pemerintah Desa terhadap Program Simpan Pinjam Badan Usaha Milik Desa Bodag - achmad irwan guzali guzali (Universitas Negeri Surabaya, 2025)
This study examines the effectiveness of village government supervision over the implementation of Village-Owned Enterprise (BUMDes) programs, focusing on the savings and loan program of BUMDes Artha Tirta Niaga in Bodag Village, Panggul Subdistrict, Trenggalek Regency. The objective of this research is to analyze the effectiveness of village government supervision using William N. Dunn’s policy evaluation framework, which consists of three indicators: adequacy, responsiveness, and appropriateness. The research problem arises from the misuse of fund management within the savings and loan program, which led to the temporary suspension of the program by the village government and raised questions regarding the effectiveness of the supervisory function. This study employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. The findings indicate that the effectiveness of village government supervision can be categorized as moderately effective. In terms of adequacy, supervision has involved various stakeholders, including village officials, the community, and the Village Community Empowerment Agency; however, it remains largely administrative rather than substantive. Regarding responsiveness, the village government has demonstrated a relatively prompt response to community reports through internal audits and village deliberation meetings, although follow-up actions have not been fully optimal. Meanwhile, in terms of appropriateness, the decision to suspend the program and establish a new management structure is considered appropriate as a corrective measure to improve BUMDes governance. Overall, the effectiveness of village government supervision over the BUMDes savings and loan program in Bodag Village is deemed fairly good, yet it requires enhanced supervisory capacity, stronger community participation, and the implementation of more systematic and sustainable audit mechanisms to achieve optimal outcomes. Keywords: Effectiveness, Supervision, Village Government, BUMDes, Loan and Savings Program, William N. Dunn.